From The Magic Tree: Oud to Look Good, Smell Good & Feel Good (Fragrance & Perfume Part 3) - Cheng, Jack Kie; Fazeeda, Mohamad (2017)
Fragrance has indeed been fascinating since the dawn of time. Some of the rarest raw material gum resins such as Frankincense and Myrrh were used by the ancients as gifts to their Gods. But many did not understand how to use this precious raw material from the trees. Therefore, historically, there was the idea of burning them. Early users realised that if they burned the gum resin, the fragrance released through the smoke would ascend towards heaven. The word perfume itself comes for the Latin word “per fumus’’, which means “through smoke”. This means that much of the fragrances of ancient times were incense-based.